Marriage Satisfaction on Young Women with Premarital Pregnancy - Aresta A. O. Batmaro; Luh Putu Ruliati; Indra Yohanes Kiling (Universitas Nusa Cendana, 2020)
Marriage due to premarital pregnancy become increasingly more common in Indonesia, although the behaviour is still deemed as inappropriate by the society and tend to be negatively stigmatized. This might affect the marriage satisfaction which could harm the overall quality of the marriage. The purpose of this study was to determine marital satisfaction on youth with premarital pregnancy. Participants in this study were nine young women who were married due to premarital pregnancy and residing in Kupang City. Data was collected using interviews and analysed with thematic analysis approach that revealed three main themes. The results showed that marital satisfaction varied in participants, in which six participants were more satisfied and enjoyed their current married life, while the other three participants were not satisfied due to dissatisfaction with aspects of equality of roles in household, parenting and sexual life. Implications from this results were discussed further in the article.